Species Variation and Collection Time on the Nutrients and Microbial Loads of Some Frozen Marine Fishes Sold in Dambatta Local Government Area of Kano State, Nigeria - Ibrahim, Kasim L.; Bichi, Armaya'u H.; Folorunso, Lateef A.; Dauda, Akeem B. (Syiah Kuala University, 2025)
The study evaluated the influence of collection time and species type on the nutritional compositions and microbial loads of some frozen marine fish species sold in the Dambatta local government area of Kano State. Three fish species; Atlantic herring (Clupea harengus, Linnaeus, 1758), Atlantic mackerel (Scomber scombrus, Linnaeus, 1758), and Atlantic horse mackerel (Trachurus trachurus, Linnaeus, 1758) were assessed. Nine pieces of each fish species were collected at three different times designated as 1st, 2nd, and 3rd collection times between when a new supply is received and almost finished, making a total of 27 fish from the cold room in Dambatta town. The proximate, free fatty acid, mineral compositions and microbial loads of the samples were analyzed. The results indicated that both the species type and collection time significantly affected all the proximate composition and free fatty acids, except carbohydrates. that was not different among the collection times. Crude protein was significantly higher in T. trachurus than in other species and the highest was 21.93 0.04% collected at the 3rd time. The highest lipid (4.97 0.02%) was also in T. trachurus but at the 2nd collection. Free fatty acid was also significantly higher in T. trachurus. All the minerals were also influenced by the species but collection time affected only the iron and manganese. For the microbial population, Salmonella sp. was influenced by both the species and collection time, it was higher significantly in T. trachurus, and the least was recorded in the first collection. E. coli was higher significantly in S. scrombrus than others and the highest was observed in the 2nd collection. T. trachurus is the best in terms of nutritional composition while the first collection had a higher microbial load, all the microbial loads were within the safety level for fish consumption.